2007
DOI: 10.1007/s10549-007-9834-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber is associated with serum sex hormones and insulin-related peptides in postmenopausal breast cancer survivors

Abstract: High fiber diets may be beneficial to postmenopausal breast cancer survivors due to fiber's favorable influence on sex hormones and peptides known to affect breast cancer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Many studies suggested a strong positive correlation between blood leptin concentration, BMI and intake of dietary fiber, On the other hand, serum leptin concentrations were not related to dietary patterns in the US population [33] and no significant correlation was found between leptin and dietary fiber [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggested a strong positive correlation between blood leptin concentration, BMI and intake of dietary fiber, On the other hand, serum leptin concentrations were not related to dietary patterns in the US population [33] and no significant correlation was found between leptin and dietary fiber [34]. …”
Section: Discussionmentioning
confidence: 99%
“…The energy content of the baseline diet is determined using the individual’s habitual energy intake (dietary history), body weight history and a calculated estimate using the Harris & Benedict formula [29] multiplied by an estimate of their Physical Activity Level (PAL). Special attention is paid to alcohol intake (maximum of one drink per day) and fibre intake (minimum of 25 grams per day) since these may influence sex hormone levels [30-32]. The run in period and the baseline diet aim to normalise the dietary pattern, stabilise body weight, check the estimated energy requirements and evaluate protocol adherence.…”
Section: Methodsmentioning
confidence: 99%
“…Responses were used to calculate grams per day of alcohol intake. Since our earlier work showed independent associations between fiber and fat intake and hormone levels, we also included data for these dietary variables in the analysis [26]. The nutrient database used to convert food information into nutrients is derived from the University of Minnesota’s Nutrition Coordinating Center’s Nutrition Data Systems for Research (NDS-R, version 2005).…”
Section: Methodsmentioning
confidence: 99%